Genetic Structure of the Tree Peony (Paeonia rockii) and the Qinling Mountains as a Geographic Barrier Driving the Fragmentation of a Large Population - Yuan, Jun–hui; Cheng, Fang–Yun; Zhou, Shi–Liang (PloS one, 2012)
Tree peonies are great ornamental plants associated with a rich ethnobotanical history in Chinese culture and have recently been used as an evolutionary model. The Qinling Mountains represent a significant geographic barrier in Asia, dividing mainland China into northern (temperate) and southern (semi-tropical) regions; however, their flora has not been well analyzed. In this study, the genetic differentiation and genetic structure of Paeonia rockii and the role of the Qinling Mountains as a barrier that has driven intraspecific fragmentation were evaluated using 14 microsatellite markers. Twenty wild populations were sampled from the distributional range of P. rockii. Significant population differentiation was suggested (F(ST) value of 0.302). Moderate genetic diversity at the population level (H(S) of 0.516) and high population diversity at the species level (H(T) of 0.749) were detected. Significant excess homozygosity (F(IS) of 0.076) and recent population bottlenecks were detected in three populations. Bayesian clusters, population genetic trees and principal coordinate analysis all classified the P. rockii populations into three genetic groups and one admixed Wenxian population. An isolation-by-distance model for P. rockii was suggested by Mantel tests (r = 0.6074, P<0.001) and supported by AMOVA (P<0.001), revealing a significant molecular variance among the groups (11.32%) and their populations (21.22%). These data support the five geographic boundaries surrounding the Qinling Mountains and adjacent areas that were detected with Monmonier's maximum-difference algorithm. Our data suggest that the current genetic structure of P. rockii has resulted from the fragmentation of a formerly continuously distributed large population following the restriction of gene flow between populations of this species by the Qinling Mountains. This study provides a fundamental genetic profile for the conservation and responsible exploitation of the extant germplasm of this species and for improving the genetic basis for breeding its cultivars.